The Ability of the Independent Auditor to Audit the Application Requirements of Electronic Commerce (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The purpose of this research is to determine the extent to which independent auditors can audit the requirements of e-commerce related to (infrastructure requirements, legislation and regulations, tax laws, and finally human cadres). To achieve this, a questionnaire was designed for auditors. Numerous statistical methods, namely arithmetic mean and standard deviation, have been used through the implementation of the Statistical Packages for Social Sciences (SPSS) program.The research has reached several results, the most important of which are: There are noobstacles to enabling the auditor to audit the application of the e-commerce requirements as well as the respective(infrastructure requirements, legislation and regulations, tax laws, and finally human cadres), and the ability of the auditor to keep up with the development of modern electronic information technology.The research has reached several recommendations, the most important of which is: Theauditor must take into consideration that the process of auditing the application of the requirements of e-commerce from the core of his work so that the audit diligently and abide by standards and professional ethics, and they need to develop the auditor's ability to audit technical support services, which will this leads to a more appropriate e-commerce environment through web site confirmations to give them reliability such as (Sys Trust), which refers to companies' compliance with information security controls, as well as a (Web Trust) certificate, economic unit website.